Combination Of Extension And Triggering Methods Of Changes In Family Head Attitudes About Stop Open Defecation Free (ODF) - Al Murhan; Aprina Aprina (Jurnal Kesehatan Prima, 2020)
Open defecation free health behavior problems in Indonesia are still prevalent, one of which is in Bumiharjo Village in 2016 ODF behavior is still carried out by 561 families. In 2018 the village of Bumiharjo will start carrying out Community Led Total Sanitation (CLTS) counseling and triggering activities. The combination of counseling and triggering methods for changing attitudes related to ODF has not yet been the basis of this research. This type of quantitative research with a quasi-experimental design. Has been carried out in March - November 2019, research subject of the head of the family who is still doing open defecation. A sample of 60 respondents divided into two groups, the sample taken by purposive sampling. Retrieval of data using a questionnaire with the results found the value of p = 0.001 so that it can conclude there is a change in attitude about stopping Open Defecation Free  before and after triggering and counseling to the Head of the Family in Purwosari Village, Natar District, South Lampung Regency. It recommended that counseling and triggering activities carried out on an ongoing basis and the availability of facilities for open defecation free, funds, and collaboration across programs and sectors.